2020
DOI: 10.1111/boc.202000030
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin suppresses spermatogenic cell apoptosis to alleviate diabetes‐induced testicular damage by inhibiting autophagy via the PI3K/AKT/mTOR axis

Abstract: Background informationDiabetes‐induced testicular dysfunction is characterised by abnormal apoptosis of spermatogenic cells, but the underlying mechanism is poorly understood. This study aimed to investigate the roles of clusterin (CLU) in testicular damage associated with diabetes pathogenesis, as well as the molecular mechanism.A rat diabetes model was established using streptozocin, and the mouse spermatogenic cell line GC‐1 spg was treated with high glucose as a cellular model. CLU was overexpressed in GC‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Previous reports demonstrated that clusterin enhances neuronal survival via activating the PI3K/Akt and other related signaling pathways. [37][38][39]64 Accordingly, we found that serpinA3N enhanced the activation of the Akt pathway in vivo and in vitro, which is associated with a neuroprotective effect. [65][66][67][68] A drawback of the present study is that we did not perform ser-pinA3N knockout or knockdown, given that serpinA3N itself is upregulated post-MCAO.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Previous reports demonstrated that clusterin enhances neuronal survival via activating the PI3K/Akt and other related signaling pathways. [37][38][39]64 Accordingly, we found that serpinA3N enhanced the activation of the Akt pathway in vivo and in vitro, which is associated with a neuroprotective effect. [65][66][67][68] A drawback of the present study is that we did not perform ser-pinA3N knockout or knockdown, given that serpinA3N itself is upregulated post-MCAO.…”
Section: Discussionmentioning
confidence: 65%
“…Previous reports demonstrated that clusterin enhances cell survival via activating the PI3K/Akt pathways in retinal glial cells and in other peripheral tissues such as the pulmonary artery, the liver, and the sperm cells. [37][38][39][40] To explore whether this serves as a potential mechanism for serpinA3N-afforded neuronal cell survival, we detected the Akt activation and its downstream protein, mechanistic target of rapamycin (mTOR), both in vitro and in vivo. In neuronal cultures subjected to OGD/R, serpinA3N treatment increased both Akt activation and mTOR activation, indicated by the ratios of phospho-Akt (Figure 6A-B).…”
Section: Serpina3n Increases Activation Of Akt Signaling Pathwaymentioning
confidence: 99%
“…Recently, abnormal apoptosis of spermatogenic cells has been identified as a key cellular event related to DM-related testicular dysfunction [20]. In addition, a previous study showed that autophagy was an effective mechanism which was capable of promoting spermatogenic cell apoptosis in response to adverse conditions (such as HG) [6]. Inhibition of apoptosis and autophagy of spermatogenic cells is considered to be a promising strategy for the treatment of DM-induced abnormal testicular function [21, 22].…”
Section: Discussionmentioning
confidence: 99%
“…Male DM patients will have a series of symptoms such as testicular endocrine dysfunction, testicular sperm level, and decreased exercise capacity [5]. The main pathological manifestation of testicular dysfunction caused by DM is decreased spermatogenesis, which may be attributed to decreasing proliferation of spermatogenic cells and increased apoptosis [6]. Therefore, exploring the regulation mechanism of the abnormal proliferation and apoptosis of spermatogenic cells in DM is of great significance for novel therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…Clusterin was elevated in diabetic nephropathy and inhibited apoptosis of podocytes [ 16 ]. Importantly, clusterin was downregulated in testis tissues of diabetic rats, and upregulation of clusterin could rescue cell viability and inhibited cell apoptosis in HG-treated GC-1 spg cells via regulating phosphoinositide 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) signaling [ 17 ]. Accordingly, elucidating the upstream regulatory mechanism of clusterin maybe help us better understand the mechanism of DTID.…”
Section: Introductionmentioning
confidence: 99%